Acute myocardial infarction caused by blast injury of the chest. Issue 4 (October 1981) - Keren, A; Stessman, J; Tzivoni, D
Abstract : A 51-year-old healthy man was hit in the chest by the shock-waves generated by an explosion, without being injured by any physical object. He felt immediate chest pain, but, in spite of electrocardiographic tracings highly suspicious for an acute anteroseptal infarction in the emergency room, he was discharged from hospital. The electrocardiogram recorded three weeks later was pathognomonic of anteroseptal infarction. Coronary arteriography performed four months later showed a complete obstruction of the left anterior descending coronary artery, with retrograde filling from the right coronary artery. It is assumed that the myocardial infarction was caused by the blast injury which induced an intimal tear and/or a subintimal haemorrhage in the left anterior descending artery with subsequent thrombosis. The lack of atherosclerosis in any other coronary arteries in this patient is noteworthy.